The Analysis Study of Diagnosis and Management of Head Injury: A Comprehensive Systematic Review - Asra Dewita Namora Harahap; Adit Muhammad Prasetya Hutagalung (The International Journal of Medical Science and Health Research, 2025)
Background: The long-term consequences of head injury can vary widely depending on factors such as injury severity, repeated trauma, and pre-existing conditions. This systematic review aims to evaluate the diagnosis and management of head injuries based on literatures of the last decade. Methods: The study followed PRISMA 2020 guidelines, reviewing English-language publications from 2015 to 2025. Editorials, duplicate reviews from the same journal, and papers lacking a DOI were excluded. The literature search was conducted using PubMed, SagePub, SpringerLink, and Google Scholar. Result: A total of 2,172 articles were initially identified through online databases (PubMed, SagePub, SpringerLink, and Google Scholar). After three rounds of screening, eight relevant studies were selected for full-text analysis. Conclusion: Advancements in neuroimaging, biomarkers, and treatment strategies have improved the diagnosis and management of head injury. However, challenges remain in standardizing definitions, predicting long-term outcomes, and developing targeted interventions. Future research should focus on refining diagnostic criteria, expanding biomarker utility, and optimizing rehabilitation approaches to enhance patient outcomes.